(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2025)
Several Molecular Pharmaceutics publications that garnered a lot of citations in 2023 are highlighted in this collection. These widely referenced publications provide insightful information about the study areas that readers are presently most interested in. They showcase ground-breaking findings in addition to pertinent analyses and viewpoints on important topics of the day.